Wireless operated parking system - Arafeh, Shady; Wazwaz, Shery; Al-Junedi, Mahmoud (جامعة بوليتكنك فلسطين - اتصالات, 2011)
In the past the parking administration used to be manually , and so it has some drawbacks such as: large time consuming , loss of accuracy , and people recently tend not to hold money in their pockets to pay for a parking ticket. Today we notice that it is necessary to automate the parking process, which will decrease the needed time for parking, increase the accuracy of the payment process, and reduces the role of a human administrator at the park. We look forward using this project to automate the parking process , by designing a system consists of sensors and counters that monitor the state of the spaces at the parking and feed back the administration center with data about the parking spaces , and this administration center communicate with the driver and opens the gate if there is a space and if this driver is permitted to enter this parking. In other words the driver communicate with the administration center and ask it to enter the garage, the administration center check the identity of the driver and the park status , and then sends a signal to the gate to open.
no of pages 160, 25081, اتصالات 10/2011 , in the store
Keywords: parking systems